A combined approach for individualized lymphadenectomy in gastric cancer patients - Zsolt Varga; Adrienn Bíró; Miklós Török; Dezső Tóth (Frontiers Media S.A., 2023)
Introduction: Gastric cancer ranks as the fifth most common cancer globally. The presence of lymph node metastasis is a significant prognostic factor influencing survival. Postoperative morbidity and nodal staging accuracy are heavily affected by the extent of lymph node dissection. Our study aimed to explore the potential integration of two contemporary methods, sentinel node navigation surgery (SNNS) and the Maruyama Computer Program (MCP), to improve the accuracy of nodal staging.Materials and methods: We conducted a prospective data collection involving patients with gastric adenocarcinoma from 2008 to 2018 at the Department of Surgery, University of Debrecen, Hungary. Data from 100 consecutive patients were collected. The primary and secondary endpoints included evaluating the rate of node-negative patients and the diagnostic accuracy of our combined approach.Results: Sentinel node mapping was successful in 97 out of 100 patients. We found that using the threshold value of the Maruyama Index (MI) ≥ 28, all metastatic stations of sentinel-node-negative patients could be identified. Our method achieved 100% sensitivity and negative predictive value, with a specificity of 60.42% (95% CI = 46.31%-72.98%).Discussion: The combined application of SNNS and MCP has proven to be an effective diagnostic technique in the synergistic approach for identifying metastasis-positive lymph node stations. Despite its limitations, this combination may assist clinicians in customizing lymphadenectomy for gastric cancer patients.